Cell–scaffold interactions in tissue engineering for oral and craniofacial reconstruction - Fushi Wang; Xinjie Cai; Ya Shen; Liuyan Meng (Bioactive Materials, 2023)
Tissue engineering (TE) is critical in oral and craniofacial reconstruction. One of the most popular topics on the biomaterial-based tissue regeneration process may be the interaction between cells and scaffolds. An increasing number of studies have identified the variables affecting cell–scaffold interaction. The creation and investigation of new scaffolds for TE and regenerative medicine based on specific interactions have become possible owing to these findings. This review discusses the effects of various types of scaffold materials on cells in TE. Because the intrinsic properties of scaffolds are essential, the influence of the physical, chemical, mechanical, and biological characteristics of scaffold materials on cell–scaffold interaction that has been discovered in recent research is elaborated in this review. The components carried by scaffolds, the degradation process, and the role of degraded products in cell–scaffold interactions are examined. Further, the roles of cells, including cell types, functions, and adhesion mechanisms, and extracellular matrix are discussed. Finally, the latest research progress on cell–scaffold interactions among various engineered tissues or organs in the oral and craniofacial region is summarized. A deeper understanding of cell–scaffold interactions is anticipated to benefit the development of TE and regenerative medicine.